Suture button systems for coronoid fracture fixation: a biomechanical time-zero pilot study - Sebastian Lappen; Pavel Kadantsev; Daniel Bohnet; Stephanie Geyer; Maximilian Hinz; Christian Marx; Sepp Braun; Sebastian Siebenlist (BMC Musculoskeletal Disorders)
Abstract Purpose This study aims to describe a fixation technique for coronoid fractures using suture buttons, and to biomechanically evaluate this technique in comparison to screw fixation as a time-zero pilot study. Methods An O’Driscoll type 2 anteromedial coronoid facet (AMCF) fracture was simulated in 20 fresh-frozen human elbows. The specimens were randomized into two groups and fracture fixation was performed with either a suture button system or a 3.5 mm cannulated screw. Ultimate load-to-failure (N) was then tested for each specimen. Results The mean load-to-failure was 322.6 ± 75.9 N for suture button fixation and 314.2 ± 85.9 N for screw fixation. The differences were not statistically significant (p = 0.432). Additional fracturing of the coronoid fragment was observed in two specimens with screw fixation. Conclusion Promising biomechanical evaluations show that this fixation technique using suture buttons in the treatment of coronoid fractures provides equal construct stability as screw fixation. Further studies are required to fully validate this procedure.